2021
DOI: 10.2147/ccide.s295423
|View full text |Cite
|
Sign up to set email alerts
|

A Phthalocyanine Derivate Mouthwash to Gargling/Rinsing as an Option to Reduce Clinical Symptoms of COVID-19: Case Series

Abstract: Aim This case series demonstrated that phthalocyanine derivate mouthwash is a promising alternative for reducing the viral load of SARS-CoV-2 and for clinical improvement of infected patients who presented mild and moderate symptoms. Purpose The aim of this study was to report a case series of patients diagnosed with COVID-19 that used the phthalocyanine derivate mouthwash to reduce clinical symptoms. Patients and Methods Eight patients used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 11 publications
1
24
0
2
Order By: Relevance
“…This is another relevant result of the positive action of APD, since a reduction in the viral load of SARS-CoV-2 above 90% has already been demonstrated in previous in vitro studies [ 8 ], [ 9 ], as well as the rapid clinical improvement of COVID-19 symptoms [ 10 ]. In a randomized study conducted in a hospital environment, COVID-19 patients with mild and moderate cases underwent an adjuvant APD mouthwash protocol.…”
Section: Letter To the Editormentioning
confidence: 52%
“…This is another relevant result of the positive action of APD, since a reduction in the viral load of SARS-CoV-2 above 90% has already been demonstrated in previous in vitro studies [ 8 ], [ 9 ], as well as the rapid clinical improvement of COVID-19 symptoms [ 10 ]. In a randomized study conducted in a hospital environment, COVID-19 patients with mild and moderate cases underwent an adjuvant APD mouthwash protocol.…”
Section: Letter To the Editormentioning
confidence: 52%
“…2 , 4 , 6 Two case series studies have shown that solutions used for gargling/rinsing with the phthalocyanine derivative contributed to the clinical improvement and general health of individuals infected with COVID-19. 10 An in vitro study demonstrated a promising antiviral action against SARS-CoV-2 in non-cytotoxic concentrations with efficiency between 92% and 99%. The same study also reported a significant decrease in hospital stay, to 4 days, with no evolution in the severity of cases, in individuals contaminated by COVID-19 who used 5 mL of the solution with the phthalocyanine derivative for 1 minute, 5 times a day.…”
Section: Discussionmentioning
confidence: 99%
“…According to the present study, the use of Mouthwash APD and Dental Gel APD, in maximum and non-cytotoxic concentration, at different times (30 seconds, 1 and 5 minutes) of exposure and contact with the SARS-CoV-2 viral solution, inactivated viral load by 90% and 99.99%, respectively, compared to the positive control, which corroborates the results of previous studies. 4 , 10 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they are dyes awaiting which, with the combination of a sensitizing drug with visible light, will promote the selective destruction of viruses, bacteria and other microorganisms 20 .The potential of phthalocyanines for biological and medical applications has been recognized 20 23 , especially in photodynamic therapy, since phthalocyanines in the excited state can promote the reactive oxygen species generation or redox processes, while no such properties are observed in the absence of light. Recently, our research group observed the promising performance of an anionic phthalocyanine derivative (APD) used in a mouthwash protocol without photoexcitation; this protocol improved the general clinical condition of patients with SARS-CoV-2 infection 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%